2012
DOI: 10.1111/j.1463-1318.2011.02819.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for colorectal anastomotic stenoses and their impact on quality of life: what are the lessons to learn?

Abstract: Since diverticulitis and mechanical anastomosis are risk factors for anastomotic stenosis, surgeons should take this into account when they are considering what type of anastomotic technique to utilize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
6
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 18 publications
4
78
6
5
Order By: Relevance
“…The mean quality score of all studies was 6 (range: 2-10). 23,27,31,36,38,40,44 23,27,31,36,38,40,44 …”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The mean quality score of all studies was 6 (range: 2-10). 23,27,31,36,38,40,44 23,27,31,36,38,40,44 …”
Section: Study Qualitymentioning
confidence: 99%
“…36 Both physical and emotional components were affected in 2 studies. 40,41 One study showed that only symptom scores were affected instead of the physical or emotional component scores. 26 Multivariate analyses were performed in 17 studies.…”
Section: Effect Of Saes On Postoperative Qolmentioning
confidence: 99%
“…The etiology of this phenomenon after surgery has not been clarified. Opted theories are other conditions such as an irritable bowel syndrome, adhesions, stenosis, incomplete sigmoid resection or changed sympathetic innervation [31]. In accordance with these assumptions, the reported re-operation rates are low and range between 0 and 3% [3].…”
Section: Discussionmentioning
confidence: 86%
“…Some of the identified risk factors for anastomotic leakage are male gender, nutritional status, high BMI, the location of anastomosis, diverting stoma, and history of radiation [10][11][12][13]. Men, because of the narrow pelvis, offer greater challenge during pelvic dissection, and hence increased risk of anastomotic leakage [14].…”
Section: Discussionmentioning
confidence: 99%